2002
DOI: 10.1016/s0168-1702(01)00432-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute hepatic failure in IFN-γ-deficient BALB/c mice after murine coronavirus infection

Abstract: We previously showed that an intraperitoneal infection with mouse hepatitis virus (MHV) persists in interferon-gamma (IFN-gamma)-deficient C57BL/6 (B6-GKO) mice and results in subacute fatal peritonitis, which bears a resemblance to feline infectious peritonitis. To examine the role of other host factors in MHV infection in mice, IFN-gamma-deficient mice with a BALB/c background (BALB-GKO) were infected intraperitoneally with MHV and compared with B6-GKO mice. In contrast to B6-GKO mice, BALB-GKO mice died wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Several studies have indicated that resistance against viral infections is dependent on mouse strain [1,8,9,11,17]. Namely, numerous host factors, both major histocompatibility complex (MHC)-dependent and MHCindependent, account for viral resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that resistance against viral infections is dependent on mouse strain [1,8,9,11,17]. Namely, numerous host factors, both major histocompatibility complex (MHC)-dependent and MHCindependent, account for viral resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Gamma interferon (IFN-c) is required for the protection against lethal infection with MHV-JHM and -A59 (Kyuwa et al, 1998(Kyuwa et al, , 2002Schijns et al, 1996Schijns et al, , 1998Smith et al, 1991). Both viral replication and hepatocellular injury are increased after infection of IFN-c receptor-deficient mice with MHV-A59 (Schijns et al, 1996).…”
mentioning
confidence: 99%
“…The A59 strain of MHV (MHV-A59) was isolated in 1961 from a colony of BALB/c mice that was being used to serially propagate leukemia (22). There are a number of different animal disease models based upon MHV infection, including models of virus-associated demyelination and viral hepatitis (12,18). These models provide important insights into the pathogenesis of virus infections.…”
mentioning
confidence: 99%